Unveiling the aesthetic connection: Balinese wayang characters and the 'prodigal son' bible story - Andreas James Darmawan; I Nyoman Sedana; Martinus Dwi Marianto (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2023)
The Prodigal Son, a well-known biblical parable cherished by children, has never been depicted using Balinese wayang, presenting an opportunity for cultural enrichment. This research aims to select appropriate Balinese wayang characters for the Bible story "The Lost Child." The motivation behind this study is to bridge the gap between the western visual style often associated with biblical depictions and the captivating Balinese wayang tradition, rekindling children's interest and appreciation for the narrative. The qualitative research method utilizes Thomas Aquinas' Christian theoretical literature and Balinese aesthetic theory, complemented by interviews and FGDs with fellow Doctoral students. The findings yield a deep correlation between the aesthetic theories, laying the foundation for selecting wayang characters. Wayang Tualen represents the father's kind traits, while Merdah embodies the adventurous youngest son. Sangut portrays the passionate firstborn, Cenk and Blonk represent dynamic and critical aspects, and Delem embodies arrogance and cunning. The research discussions enrich the study's scope, contributing to Balinese cultural preservation and its fusion with global characterizations. This artistic amalgamation fosters cross-cultural appreciation and artistic regeneration among younger generations with both the characters in the story and the characters in the Balinese wayang.